2009
DOI: 10.1097/md.0b013e3181af70c1
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu Arteritis and Giant Cell Arteritis

Abstract: Giant cell arteritis (GCA) and Takayasu arteritis (TAK) have been considered distinct disorders based on their clinical features, age of onset, and ethnic distribution. However, on closer examination, these disorders appear more similar than different. The histopathology of arterial lesions in these diseases may be indistinguishable. Imaging studies have revealed large vessel inflammation in at least 60% of patients with GCA. We questioned whether the distinctions between these diseases might in part be an art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(51 citation statements)
references
References 41 publications
2
38
0
1
Order By: Relevance
“…Fourth, we used the ACR criteria to differentiate TAK from GCA and to exclude GCA. TAK and GCA appear more similar than different, based on clinical and pathological findings [16]. In contrast, Michel et al insisted that GCA and TAK were easily definable and separable disorders, even when the typical age barrier of 40 years at onset of disease was excluded [17].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we used the ACR criteria to differentiate TAK from GCA and to exclude GCA. TAK and GCA appear more similar than different, based on clinical and pathological findings [16]. In contrast, Michel et al insisted that GCA and TAK were easily definable and separable disorders, even when the typical age barrier of 40 years at onset of disease was excluded [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, GCA and TA have been considered distinct disorders based on their differing ages of onset and ethnic distributions. However, reports have claimed that these disorders have more similarities than differences, including similarities in several clinical features, angiographic findings, and the histopathological characteristics of arterial lesions [28, 29]. Thus, our results indicate that FCGR2A/FCGR3A might be a susceptibility gene for TA in patients from the Chinese Han population, suggesting that TA might share associated genetic loci with other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 49%
“…In giant cell arteritis (GCA), a randomized trial examining abatacept that was conducted by this same investigator group using an identical design, found that abatacept combined with glucocorticoids resulted in a longer duration of relapse-free survival than treatment with prednisone alone (35). GCA and TAK share many common features in both being large-vessel granulomatous vasculitides that can have similar arterial distributions (36, 37) and laboratory-based studies have supported both as being antigen-drive diseases (38, 39). It is an ongoing question whether GCA and TAK are unique entities or if they represent part of a single clinical spectrum (36).…”
Section: Discussionmentioning
confidence: 99%